The nature of equilibrium and evolution of the water - CO2 - alumosilicate system in the lithosphere; Proceedings of the second International Symposium on Water-Rock Interaction, Strasburg, 1977, Sec. 1 - Shvartsev S. L. Stepan Lvovich (1977, 1977)
В фонде НТБ ТПУ отсутствует